Drought tolerance in seedlings of coffee genotypes carrying genes of different species - Carvalho, Filipe Gimenez; Sera, Gustavo Hiroshi; Andreazi, Elder; Sera, Tumoru; Fonseca, Inês Cristina de Batista; Carducci, Fernando Cesar; Shigueoka, Luciana Harumi; Holderbaum, Melina Marques; Costa, Kamila Carmezini (Coffee Science - ISSN 1984-3909, 2017)
Drought is one of the limiting factors to Arabica coffee crop and tolerance sources exist in different Coffea spp. species. The aim of this research was to evaluate the drought tolerance in seedlings of 21 coffee genotypes, carrying genes of different species, by wilting degree analysis of seedling leaves subjected to a period of hydric restriction. The experimental design was completely randomized with 24 replicates, with one seedling of six months per plot. The experiment was carried out in a greenhouse at the Instituto Agronômico do Paraná (IAPAR) in Londrina, Paraná, Brazil. Two evaluations were performed using a leaf wilting index, in the range of grades from 1 to 9, that were performed, in both evaluations, six days after the drought restriction began. Assessments of the intensity of wilt in seedlings allowed to discriminate genotypes with tolerance to drought. The most tolerant genotype to drought was IAPAR 11260 a Coffea arabica (carrier of Coffea racemosa genes), followed by Coffea arabica Ethiopia E368, ‘IPR 100’ (carrier of Coffea liberica genes) and ‘IPR 103’ (carrier of Coffea canephora genes). Coffea canephora cv. ‘Apoatã IAC 2258’ was the most sensitive compared with all Coffea arabica genotypes.